Peculiarities of Indian English as a separate language - Georgievna Grishechko, Elizaveta (2021)
The following paper will reveal the varieties of English pronunciation in India, its features and characteristics. This research helped us to consider the history of occurrence of English in India, the influence of local languages on it, the birth of its own unique English, which is used in India now. The research highlights the impact of English on Indians in general and its modification as the individual language differs from other English variants. The paper illustrates the features of translation and vocabulary in Indian English, which will explore the specification uses of it. The research also provides variations of Indian English as dialect and pronunciation in India because it changes from north to south and east to west. To complete our study, we used a lot of methods, such as observation, comparative, elicitation approaches, collection and analysis of diverse information. Such topic and results of this research could help us to learn the differences in language implementation in different countries and could give some ideas to improve teaching methods that are used in schools and universities all over the world. In conclusion, we found out that the English language has considerably changed since its occurrence, and all these transformations are results of globalisation, the realisation of new technologies, development of media and strengthening of communication between different countries.